DETERMINATION OF PINAVERIUM BROMIDE IN PHARMACEUTICAL DOSAGE FORMS BY A VALIDATED STABILITY-INDICATING LC METHOD - Maximiliano da Silva Sangoi; Anna Karolina Mouzer da Silva Machado; Lorena Coimbra Florindo; Brenda Rocha Gonçalves; Vítor Todeschini (Drug Analytical Research, 2017)
A reversed-phase liquid chromatography (LC) method is validated for the determination of pinaverium bromide (PB) in pharmaceutical dosage forms. The LC method is carried out on a reversed-phase monolithic C18 column (100 x 4.6 mm i.d.), maintained at 45 ºC. The mobile phase consisted of acetonitrile and a solution of triethylamine 0.3% pH 5.0 (50:50; v/v), run at a flow rate of 2.0 mL/min, with photodiode array detector set at 213 nm. The chromatographic separation is obtained with PB retention time of 3.4 min, and it is linear in the range of 5-100 μg/mL (r2 = 0.9991). The limits of detection and quantitation are 1.41 and 4.70 μg/mL, respectively. The specificity and stability-indicating capability of the method are proven through degradation studies, which also showed that there is no interference of the formulation excipients, showing that peak is free from any coeluting peak. The method showed adequate precision, with a relative standard deviation values lower than 1.38%. Excellent values of accuracy were also obtained, with a mean value of 100.68%. Experimental design is used during validation to calculate and prove method robustness. The proposed LC method is applied for the analysis of the PB pharmaceutical dosage forms, contributing to improve the quality control and to assure the therapeutic efficacy.